Brasões episcopais: registro e memória visual da Bahia no Século XVIII - Santos, Ricardo Costa dos (2011)
This dissertation aimed to conduct a historical and aesthetic analysis of the archbishops of the Diocese da Bahia coats of arms of the eighteenth century. For this, we made a study of the history of heraldry and its rules of development, emphasizing specifically the armory that focuses on weapons-of-faith: the ecclesiastical heraldry. Also, we highlighted the historical moment in which the coats of arms were designed and the institution that promoted them, the Church. Therefore, the coat is seen as a drawing and the drawing as record and memory. Furthermore, as artistic expression and as such, is not separated from its time. So, we considered the heraldry in the context of current aesthetic movement in the eighteenth-century in Bahia and so we tried to understand in the coats of arms studied the relationship between the heraldic design and the Baroque movement. In short, this dissertation is a reflection on the history of heraldry, Brazilian heraldry and, in particular, on the Episcopal heraldry in the eighteenth-century in Bahia. We emphasize the heraldic design as an important element of colonial graphic arts, and stress the historiographical and aesthetic value of episcopal coats of arms. Because of its aesthetic quality, the coats of arms contained on the tombstones were considered as an authentic manifestation of the Brazilian Episcopal heraldry, showing that existed in the eighteenth century already designers who could prepare a coat of arms.